Human and Animal Exposure to Toxocara Vitulorum in Rural Livestock-Associated Communities in Al-Qadisiyah Province, Iraq - Saleh, Osamah Hadi (American Journal of Biology and Natural Sciences, 2026)
Toxocara vitulorum is a neglected zoonotic nematode of cattle and buffalo calves, and little is known about its human exposure potential. The current study focused on human and animal exposure to T. vitulorum in the rural livestock-associated communities of Al-Qadisiyah Province, Iraq, and employed both serological and molecular methodologies. A total of 120 livestock-associated humans and 150 cattle and buffalo calves were sampled for serum. An indirect ELISA was utilized for the detection of anti-T. vitulorum IgG, and fecal samples were obtained from calves (n = 150) for analysis by quantitative PCR for the ITS-1 region. The analysis of the results of the serological study, it was found that there is a statistically significant difference in the seroprevalence of the study populations. A higher proportion of seropositivity was observed in animals (38.7%, 58/150) than in humans (17.5%, 21/120) (χ² = 13.62, p < 0.001). Among humans, seropositivity was significantly associated with daily animal contact (26.8% vs. Molecular detection showed T. vitulorum DNA in 42.0% (63/150) of animal fecal samples, with average Ct values of 29.4 ± 2.1. Animal samples that were positive by qPCR were statistically significantly more likely to be seropositive (OR = 3.46, 95% CI: 1.78–6.72, p < 0.001). Approximately, 6% of seroprevalence and the animal prevalence of the sampled sites were positively correlated (r = 0.61, p = 0.02) out of the total sites assessed. Evidence of the zoonotic risk of exposure to T. vitulorum in rural communities of Iraq is substantial, and the risk warrants concern in terms of public health from a One Health perspective.